Sexually Transmitted Infections among Human Immunodeficiency Virus Patients in a Tertiary Hospital in Surabaya, Indonesia - Suryanegara, Jose; Pilar, Nissa Avina; Riswanto, Cintya Dipta; Agusni, Regitta Indira; Sari, Maylita; Astindari; Widyantari, Septiana; Nurul Hidayati, Afif; Murtiastutik, Dwi (Faculty of Medicine, Universitas Airlangga, 2025)
Background: Human immunodeficiency virus (HIV) remains a significant global public health concern. One of its primary modes of transmission is sexual contact, leading to frequent co-infection with other sexually transmitted infections (STIs). Understanding the profile of STIs among HIV patients is essential for improving management and prevention strategies. Purpose: This study aims to describe the prevalence, types, and basic demographic characteristics (age and sex) of STIs among HIV patients treated at a tertiary referral hospital in Indonesia, to enhance understanding and optimize patient care. Methods: A retrospective observational study was conducted at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. Researchers analyzed the medical records of HIV patients who had coexisting STIs and visited the dermatology and venereology outpatient clinic between January 2021 and December 2022. Data collected included patient demographics, STI diagnoses, and clinical characteristics. Result: A total of 222 HIV patients with STIs were included, with a male predominance (85.6%) and a mean age of 28.64 years. The most common STIs were anogenital warts (47.7%), latent syphilis (18.0%), unspecified syphilis (10.8%), secondary syphilis (10.4%), and molluscum contagiosum (7.7%). The findings highlight the variations in STI prevalence based on sex and age distribution among HIV patients. Conclusion: This study points out that there are integrated management and prevention strategies targeting both HIV and STIs. Although our study did not specifically assess sexual orientation, previous research highlights men who have sex with men (MSM) as a key high-risk population.